Metabolic Flexibility of Sulfate-Reducing Bacteria - Plugge, Caroline M.; Zhang, Weiwen; Scholten, Johannes C.; Stams, Alfons J. (Frontiers in Microbiology, 2011)
Dissimilatory sulfate-reducing prokaryotes (SRB) are a very diverse group of anaerobic bacteria that are omnipresent in nature and play an imperative role in the global cycling of carbon and sulfur. In anoxic marine sediments sulfate reduction accounts for up to 50% of the entire organic mineralization in coastal and shelf ecosystems where sulfate diffuses several meters deep into the sediment. As a consequence, SRB would be expected in the sulfate-containing upper sediment layers, whereas methanogenic Archaea would be expected to succeed in the deeper sulfate-depleted layers of the sediment. Where sediments are high in organic matter, sulfate is depleted at shallow sediment depths, and biogenic methane production will occur. In the absence of sulfate, many SRB ferment organic acids and alcohols, producing hydrogen, acetate, and carbon dioxide, and may even rely on hydrogen- and acetate-scavenging methanogens to convert organic compounds to methane. SRB can establish two different life styles, and these can be termed as sulfidogenic and acetogenic, hydrogenogenic metabolism. The advantage of having different metabolic capabilities is that it raises the chance of survival in environments when electron acceptors become depleted. In marine sediments, SRB and methanogens do not compete but rather complement each other in the degradation of organic matter. Also in freshwater ecosystems with sulfate concentrations of only 10-200 μM, sulfate is consumed efficiently within the top several cm of the sediments. Here, many of the δ-Proteobacteria present have the genetic machinery to perform dissimilatory sulfate reduction, yet they have an acetogenic, hydrogenogenic way of life. In this review we evaluate the physiology and metabolic mode of SRB in relation with their environment.